The guardian: metabolic and tumour-suppressive effects of SIRT6 - Lerrer, Batya (European Molecular Biology Organization, 2013)
Cell 151 6: 1185–1199 doi:; DOI: 10.1016/j.cell.2012.10.047; published online 12 07 2012